2017
DOI: 10.4000/archeosciences.4917
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Survey And Archaeological Excavations In the Neolithic and Bronze-Age Settlement of La Dou (Girona, Spain). A combined approach to a new site

Abstract: his paper presents the results of the investigations carried out from 2009 to 2013 in the multi-period archaeological site of La Dou (Sant Esteve d'en Bas, Girona, Catalonia). he authors expose the strategy applied to create the surveys and results of the excavations conducted to verify and date the detected features. he site was discovered in 2005 in a rescue excavation due to the building of a road, revealing a group of iring pits and other stratigraphic remains of a rare Neolithic, open-air settlement, date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…The procedure was designed to obtain an accurate and empirically tested image of a spatial and chronological structure of the castle with a minimal disturbance of its remains. The multi‐method approach is becoming more and more common in the study of archaeological remains in many regions of the world, and in the literature on the subject numerous studies can be found proving the usefulness of this research strategy (e.g., Sala et al, 2017; Shi et al, 2020; Viberg et al, 2011). Reconstruction of a spatial structure is a basic step in research on the noble residences.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was designed to obtain an accurate and empirically tested image of a spatial and chronological structure of the castle with a minimal disturbance of its remains. The multi‐method approach is becoming more and more common in the study of archaeological remains in many regions of the world, and in the literature on the subject numerous studies can be found proving the usefulness of this research strategy (e.g., Sala et al, 2017; Shi et al, 2020; Viberg et al, 2011). Reconstruction of a spatial structure is a basic step in research on the noble residences.…”
Section: Introductionmentioning
confidence: 99%
“…Les méthodes de datation abordent des matériaux variés, avec la dendrochronologie (Le Roy et al, 2017), l'archéomagnétisme (Hervé et al, 2016 ;Fajal et al, 2017) ou en combinant les méthodes (Urbanova et al, 2016). Les prospections géophysiques combinent elles aussi les techniques en fonction des espaces étudiés (Mathé et al, 2016 ;Gaetan, 2017), ou ciblent une approche en fonction des terrains ou des structures recherchées (Mojica et al, 2017 ;Sala et al, 2017 ;Florsch et al, 2017). Enfin, pour les approches touchant aux paléo-environnements certaines sont purement méthodologiques (Delhon, 2016), d'autres sont consacrées à un site avec la reconstitution de l'évolution du climat en combinant sédimentologie et malacologie (Danukalova et al, 2017).…”
unclassified